2018
DOI: 10.1002/path.5040
|View full text |Cite
|
Sign up to set email alerts
|

Mixed ductal‐lobular carcinomas: evidence for progression from ductal to lobular morphology

Abstract: Mixed ductal–lobular carcinomas (MDLs) show both ductal and lobular morphology, and constitute an archetypal example of intratumoural morphological heterogeneity. The mechanisms underlying the coexistence of these different morphological entities are poorly understood, although theories include that these components either represent ‘collision’ of independent tumours or evolve from a common ancestor. We performed comprehensive clinicopathological analysis of a cohort of 82 MDLs, and found that: (1) MDLs more f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 35 publications
5
61
1
Order By: Relevance
“…In ILC mixed with other types, as in the present case, however, it is more likely that the other component transitioned to ILC by loss of E‐cadherin via genetic or epigenetic change, rather than that each component was generated independently. Reed et al reported genome analysis data of mixed ductal‐lobular carcinoma of the breast suggesting that the lobular component can arise via a ductal pathway of tumor progression . The present case may suggest the existence of an oncogenic pathway similar to the ductal pathway in PLC via a transition from apocrine carcinoma.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In ILC mixed with other types, as in the present case, however, it is more likely that the other component transitioned to ILC by loss of E‐cadherin via genetic or epigenetic change, rather than that each component was generated independently. Reed et al reported genome analysis data of mixed ductal‐lobular carcinoma of the breast suggesting that the lobular component can arise via a ductal pathway of tumor progression . The present case may suggest the existence of an oncogenic pathway similar to the ductal pathway in PLC via a transition from apocrine carcinoma.…”
Section: Discussionmentioning
confidence: 52%
“…This means aberrant expression of E‐cadherin protein that lost the functions of cell adhesion and anchoring P120 catenin. In mixed ductal‐lobular carcinomas, E‐cadherin was almost always aberrantly located in the cytoplasm in the lobular component, in contrast to the pure type of invasive lobular carcinoma, where E‐cadherin is mostly absent . There is little information on genetic changes involving aberrant expression of E‐cadherin in ILC, so that the molecular mechanism has not been clear.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the above studies, where topographically defined regions were analysed, here morphologically defined populations of cells representing the different growth patterns (ductal and lobular, including associated pre-invasive lesions) were isolated by microdissection and analysed. In individual cases, all lesions shared precise genetic alterations as likely early events in tumour development; all cases also exhibited private mutations unique to a morphological lineage (e.g., TBX3), suggesting they may be important in the separate evolution from a common antecedent [42].…”
Section: Subclonal Genomic Diversity In Primary Breast Cancermentioning
confidence: 98%
“…Mixed ductal lobular carcinomas are a unique histological subtype of breast cancer; like metaplastic breast cancers they elicit morphological evidence of intra-tumour heterogeneity, this time showing tumour regions with both ductal and lobular-like differentiation. Multi-region exome sequencing supplemented by copy number profiling of cases exhibiting distinct morphological components demonstrated these were clonally related tumour regions as opposed to being collision tumours [42]. In contrast to the above studies, where topographically defined regions were analysed, here morphologically defined populations of cells representing the different growth patterns (ductal and lobular, including associated pre-invasive lesions) were isolated by microdissection and analysed.…”
Section: Subclonal Genomic Diversity In Primary Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation